Changes in Earnings Inequality - an International Perspective - Peter Gottschalk; Mary Joyce (Luxembourg Income Study (LIS), 1991)
This paper investigates earnings and wage inequality trends in several LIS countries in the 1980's. It finds a trend toward greater wage inequality in virtually all LIS countries, thus providing some evidence that technological change may explain a larger fraction of earnings and wage inequality than does changing patterns of international trade.
Keywords: 330